2010
DOI: 10.4149/gpb_2010_02_194
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of ghrelin on the adrenal cortex: a morphological and hormonal study

Abstract: Abstract. Ghrelin, a growth hormone secretagogue that exerts an important role in appetite and weight regulation, participates in the activation of the hypothalamo-pituitary-adrenal (HPA) axis. Male Wistar rats (5/group) received daily for 5 days, via an ICV (intracerebroventricular) cannula, 5 µl phosphate buffered saline with or without 1 µg of rat ghrelin. Two hours after the last injection, blood and adrenal glands were collected from decapitated rats for blood hormone analyses and histologic and morphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Finally, while confirming the previously described HPA axisstimulating capacity of ghrelin (Milosevic et al, 2010;Mozid et al, 2003;Wren et al, 2002), our data for the first time reveal its increase with aging. As the well known stimulatory effects of cortisol/ corticosterone on blood triglycerides/cholesterol, lipolysis and adipogeneseis (van Raalte et al, 2009) have all been mirrored by ghrelin, it seems that the higher responsiveness of older animals to ghrelin in the present study could be at least in part mediated via HPA axis activation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, while confirming the previously described HPA axisstimulating capacity of ghrelin (Milosevic et al, 2010;Mozid et al, 2003;Wren et al, 2002), our data for the first time reveal its increase with aging. As the well known stimulatory effects of cortisol/ corticosterone on blood triglycerides/cholesterol, lipolysis and adipogeneseis (van Raalte et al, 2009) have all been mirrored by ghrelin, it seems that the higher responsiveness of older animals to ghrelin in the present study could be at least in part mediated via HPA axis activation.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, the influence of age on the ability of ghrelin to modulate body weight and lipid metabolism has not been extensively investigated. In addition, although ghrelin is known to inhibit secretion of anorexigenic hormones insulin and leptin (Dezaki et al, 2008;Konturek et al, 2004) and stimulate the activity of hypothalamic-pituitaryadrenal (HPA) axis (Milosevic et al, 2010;Mozid et al, 2003;Wren et al, 2002), the age dependence of these effects has not been explored so far.…”
Section: Introductionmentioning
confidence: 97%
“…This study demonstrates that aldosterone levels decreased with the four treatments. The meal effect can be explained, at least partially, by two factors, the digestive signals as it is known that several hormones decrease after eating, including ghrelin and aldosterone [14] and the 276 mg sodium provided by the standard meal, as aldosterone decreases after sodium intake [8].…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid signaling markedly stimulates natriuretic peptide receptor-A gene expression [24]. Moreover, it was found that ANP level decreases significantly after treatment with ghrelin in a rat model [25]; ghrelin elevates aldosterone [26]; and applying ghrelin supplementation to normal lungs increased retinoic acid receptor α/γ expression [27].…”
Section: Spleen Group Consists Of Anp Aldosterone Retinoic Acid Anmentioning
confidence: 99%